Professionalizing practices in Higher Technical Education. The experience of the computer sector in the argentine province of Corrientes - D’Andrea, Ana (2021)
This article aims to identify the types of skills that seek to develop the Professional Practices in the training of senior technicians in Information Technology Infrastructure Support in the province of Corrientes (Argentina). This is a descriptive study whose results are drawn from in-depth interviews with the different actors involved in the Professional Practices of an intentional sample of three careers. As a result, the development of some specific professional capacities is observed depending on the context (with limited possibilities of expansion). Students value the acquisition of basic professional skills (common to any technician regardless of the specialty).